Relationship between tooth loss and chewing ability to cognitive function of dementia patients - Delvi Sintia Reni; Bahruddin Thalib; Al’qarama Mahardhika Thalib (Makassar Dental Journal PDGI Makassar, 2020)
Introduction: Oral health in the elderly is usually worse than the general population and its can increase the incidence of edentulous and tooth loss. Studies show that a reduction in the number of teeth and users of complete dentures causing the ability to chew is significantly to be less efficient and have an impact on general health. The lack of chewing ability is at risk of causing cognitive impairment. Cognitive impairment in the elderly is an early clinical sign of dementia. A number of studies have reported that individual with cognitive impairments especially those involving memory problems are more likely to develop dementia compared to normal people. Objective: This literature review discusses the relationship between oral health such as tooth loss, impaired chewing ability, and in relation to cognitive impairment that can increase the risk of dementia.